Rhomboid Flap Technique in Breast-conserving Surgery: An Alternative Method for the Reconstruction of Lumpectomy Defects - Ebru Menekşe; Sefa Özyazıcı; Faruk Karateke; Ümit Turan; Adnan Kuvvetli; Cihan Gökler; Mehmet Özdoğan; Safa Önel (European Journal of Breast Health, 2015)

(untitled)
Objective: We aimed to present our experience with rhomboid flap reconstruction, which is a simple technique, in breast cancer patients who underwent breast-conserving surgery.Methods: We reviewed the medical records of 13 patients with breast cancer who underwent rhomboid flap reconstruction. The patients were evaluated for tumor size, safe surgical margin, and other clinical and pathological features.Results: The mean age of the patients was 43.1 years (range: 28–69 years). The mean tumor diameter was 30.8 mm (range: 15–60 mm). The mean of the safe margin of resection was evaluated to be 17.8 mm (range: 5–30 mm). Re-excision was required for one patient in the same session.Conclusion: Rhomboid flap reconstruction can facilitate the applicability of breast-conserving surgery in early breast cancer patients with large tumor-to-breast-size ratio or tumors close to the skin.